Al-Thab’u Dalam Pemikiran Pendidikan TGKH Muhammad Zainuddin Abdul Madjid Dan Relevansinya Dengan UU Sisdiknas No 20 Tahun 2003 - Made Saihu; M Adib Abdushomad; Anas Nasrudin (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
This research was conducted because it saw the relevance of the thought of al-Thab 'education in the perspective of TGKH Muhammad Zainuddin, with the National Education System Law No. 20 of 2003. The method used in this paper is the literature study method with qualitative descriptive analysis techniques by collecting data or materials. materials related to the theme of the discussion and problems taken from bibliographical sources. This paper concludes that there is a relevance of the TGKH TGKH Muhammad Zainuddin educational thinking with the National Education System, namely: 1) Educational objectives; 2) Teaching methods; 3) education delivery strategy; 4) Learning strategies. The perspective of TGKH Muhammad Zainuddin, not only aims to change the characteristics through the educational path but also aims to increase the religious value of society through the applied Sufism teachings.